Pengaruh Pemahaman Akuntansi Dasar dan Computer Knowledge terhadap Keahlian Penggunaan Aplikasi MYOB pada Siswa Kelas XI SMK Talenta Bangsa - Adi Suprayoga; Aliyah Aliyah; Sri Winda Hardiyanti Damanik (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
The purpose of this study is to determine the extent to which computer knowledge and basic accounting knowledge influence the level of proficiency in using MYOB, both independently and simultaneously. The method used is quantitative with an associative approach. The research respondents consisted of 115 students from SMK Talenta Bangsa who were collected using a saturated sampling technique. The data collection instruments were tested for validity and reliability, while the prerequisites for analysis included linearity and multicollinearity tests. Multiple linear regression analysis was used as the method, and t-tests and F-tests were used to examine the hypotheses.The analysis results indicate that basic accounting knowledge has a positive and significant impact on the ability to use MYOB, with a t-value of 8.222 > t-table 1.980. Similarly, computer knowledge was also found to have a significant impact, with a t-value of 4.941 > t-table 1.980. Simultaneously, both independent variables contribute significantly to students' skills in operating MYOB, as indicated by a significance level of 0.000 < 0.05 and an F-value of 35.602 > F-table 3.08. The regression equation yields a constant of 19.387, while the coefficient of determination (R²) is 38.9%. This indicates that the two variables can explain 38.9% of the variation in students' ability, while the remaining 61.1% is influenced by other factors outside the scope of this study.